THE PERCEPTIONS OF VLORA UNIVERSITY STUDENTS ABOUT SEXUAL BEHAVIOR AND THE RISK OF HIV INFECTION - Rezarta Lalo; Gjergji Theodhosi; Fatjona Kamberi; Yllka Stramarko (European Scientific Journal, ESJ, 2015)
Introduction: Although various studies have shown that the young albanians have a satisfactory level of knowledge about HIV / AIDS, other studies prove that there is a significant difference between the level of the knowledges and their healthy sexual behaviors. Purpose: To establish the perceptions of the students at the University of Vlora towards the sexual behaviour which could make them vulnerable to HIV and AIDS. Methodology: This is a descriptive study where quantitative method was used for the data and information resulting from a survey structured in the form of a questionnaire. The study participants were 721 randomly selected students from the Vlora University. Results: The average age of the students was 20.75 ± 2.2 years, 56.45% were female and 43.55% male. Regarding sexual behaviour, there are students who think that sexual relations make them more popular (36%), that a person cannot contract HIV the first time he/she has sex (37%), that sexual intercourse with same sex is safe (41%),there is no risk if they use alcohol or drugs before / during sexual intercourse (36%).There is a statistically significant difference between the two sexes and knowledge about sexual behavior (p <0.0001 <0.05 Chi-Square),between students with different ages at first intercourse and sexual behavior (p = 0.0036 <0.05 Chi-Square),sexual behaviors of students with different levels of knowledge about HIV / AIDS (P <0.0001 Chi-Square <0.05). Conclusions: The students have misconceptions about certain sexual behaviors. The level of knowledge about HIV / AIDS affects sexual behavior of students.